Menstrual Symptoms After COVID-19 Vaccine: A Cross-Sectional Investigation in the MENA Region - Muhaidat N; Alshrouf MA; Azzam MI; Karam AM; Al-Nazer MW; Al-Ani A (Dove Medical Press, 2022)
Nadia Muhaidat,1 Mohammad A Alshrouf,2 Muayad I Azzam,2 Abdulrahman M Karam,2 Majed W Al-Nazer,2 Abdallah Al-Ani3 1Department of Obstetrics & Gynaecology, Jordan University Hospital, Amman, Jordan; 2The School of Medicine, The University of Jordan, Amman, Jordan; 3King Hussein Cancer Center, Amman, JordanCorrespondence: Nadia Muhaidat, Department of Obstetrics & Gynaecology, Jordan University Hospital, Queen Rania Street, Amman, 11942, Jordan, Tel +962 798385775, Email Nadiadat@hotmail.comBackground: Since the emergence of COVID-19 vaccinations, many women around the world are reporting abnormalities in their menstrual periods post-vaccination. The aim of this study is to investigate the prevalence and impact of menstrual abnormalities after the COVID-19 vaccine among females residing within the Middle East and North Africa (MENA).Methods: The study utilized a cross-sectional online self-administered survey from July 2021 to August 2021 targeting females living in the MENA region above the age of menarche who had received vaccine and were not pregnant or lactating, and do not have a history of primary ovarian insufficiency, hypothalamic menopause, or have undergone a hysterectomy. The survey was distributed regionally via social media.Results: A total of 2269 females were included in our study, with a mean age of 34.3 ± 8.5 years. About 66.3% of participants reported menstrual symptoms post-vaccination, of which 46.7% experienced them after their first dose. However, in 93.6% of participants, the symptoms resolved within 2 months. Vaccine type did not significantly influence the incidence of abnormalities (p > 0.05). Participants who had confirmed previous COVID-19 infection had a very similar percentage of menstrual abnormalities compared to people who did not have COVID-19 infection or symptoms suspected of COVID-19 infection and did not test (67.5%, 66.8%, respectively); nevertheless, those who had experienced the COVID-19 vaccine general side effects had significantly more abnormalities (p < 0.001). Compared to their pandemic status, females reported significantly more abnormalities post-vaccination.Conclusion: The study showed a possible link between the COVID-19 vaccine and menstrual abnormalities that have impacted their quality of life.Keywords: COVID-19, MENA, menstrual abnormalities, menstrual cycle, vaccine